Festival concert, March 13, 1941, on the anniversary of the return of the Ostmark to the Reich - Wiener Philharmoniker:::::::::::::::; Schneider, Constantin (author)::::::::::::::: (Austria; Vienna; Wagner Druck, 2020)
Program for a festival concert on March 13, 1941, by the Vienna Philharmonic in a performance of Beethoven's Ninth Symphony conducted by Hans Knappertsbusch. Includes program notes by C. Schneider.